Impacts of Covid-19 Pandemic on Nigeria’s Economy: Effective Foundry Technology as a Sustainable Solution - Yusuf Lanre SHUAIB-BABATA; Olanrewaju Yusuf BUSARI; Rasheedat Modupe MAHAMOOD; Salihu Swarnu YARU; Lawal Babatunde ABDULQADIR; Ibrahim Owolabi AMBALI; Kabiru Suleiman AJAO; Sikiru Ottan ABDULRAMAN (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2022)
This study considered the effect of the Covid-19 pandemic on the economy of Nigeria and investigated the effective application of foundry technology to proffer a sustainable solution to the problem. Domestication of production of motorcycle components, being a significant means of transportation that is required for the development of any society was considered. Aluminium scraps from a waste dump and Belle and Oyun natural moulding sands in Kwara State, Nigeria,  which have been previously recommended for non-ferrous casting in previous studies were considered and used for casting of motorcycle/tricycle parts (centre stand and brake pedal) using AFS guidelines. The scraps’ chemical compositions  were analysed. Thereafter, some mechanical properties with the microstructure of the aluminium casts and that of commercially obtained imported types were examined using appropriate ASTM standards. Cast aluminium alloy produced using  scrap had no casting defects and had some mechanical properties comparable to those available on the markets (imported). Thus, effective usage of naturally available moulding sands in Nigeria for foundry applications would help to proffer sustainable solutions to the nation’s economic problem as a result of the adverse effects of the Covid-19 pandemic.